The Influence of Regional Original Revenue (PAD) And Balancing Funds on Capital Expenditure Budget in Kupang Regency: The Influence of Regional Original Revenue (PAD) And Balancing Funds on Capital Expenditure Budget in Kupang Regency - Fanggidae, Enjelina; Tomasowa, Thobias E. D.; Wulandari, Agusta A.; Junias, Donny T.S. (Journal of Practical Management Studies, 2025)
Theregional budget includes the basis for financial budgeting which is implemented for public services or the Regional Revenue and Expenditure Budget (APBD). The regional budget and expenditure is a detailed list of regional income and expenditure in one year which consists of various components such as Regional Original Income (PAD) and Balancing Funds including General Allocation Funds (DAU) and so on as well as expenditures which include various expenditures such as capital expenditure.OriginalRegional Income is a source of regional revenue that comes from the region itself based on its capabilities. Balancing funds are funds sourced from the State Revenue and Expenditure Budget (APBN) which are allocated to regions to fund regional needs in the context of implementing decentralization. Capital Expenditures are budget expenditures for the acquisition of fixed assets and other assets that provide benefits for more than one accounting period.Thisresearch uses quantitative research methods, with research results that Original Regional Income (PAD) has a positive effect on the capital expenditure budget. Balancing funds have a positive effect on the capital expenditure budget. Regional Original Income (PAD) and Balancing Funds have a positive effect on the capital expenditure budget in Kupang Regency.